PENGARUH JOB SATISFACTION DAN WORK ENVIRONMENT TERHADAP TURNOVER INTENTION DENGAN KOMITMEN ORGANISASIONAL SEBAGAI VARIABEL MEDIASI - Sari, Revania Selvika; Arief Subyantoro (Journal of Management and Business, 2024)
This research aims to analyze the influence of job satisfaction and work environment on turnover intention with organizational commitment as a mediating variable for Super Dazzle Gejayan Yogyakarta employees. The method used in this research is a quantitative approach. Sampling was carried out using a saturated sampling technique with a total of 80 respondents. The research results show that job satisfaction has a negative and significant effect on employee turnover intention, the work environment has a negative and significant effect on turnover intention, organizational commitment is able to mediate the effect of job satisfaction on turnover intention, and organizational commitment is able to mediate The influence of work environment on turnover intention